Multiple security certification system between blockchain based terminal and internet of things device: Implication for open innovation - Bong-Gyeol Choi; EuiSeob Jeong; Sang-Woo Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
As the number of Internet of Things (IoT) devices increases, services expand and illegal hacking and infringement methods become more sophisticated, an effective solution for blockchain technology is required as a fundamental solution to security threats. In this paper, we develop the security module of an IoT device based on blockchain technology that blocks hacking and information infringement and forms a multi-security blockchain system between the IoT device and the user device and we develop a user application. We contribute to addressing the security threats faced by IoT application services by developing a new method. In particular, we present some schemes for the development of a multi-security certification system based on blockchain for IoT security.
Keywords: 650; blockchain certification system; device third-party security certification system; multiple security certification system between IoT devices; security certification system